A* Pathfinding Applications in Two-Dimensional AI Video Games - Tomi Tri Sujaka; Kurniadin Abd Latif; Sirojul Hadi; Hasbullah Hasbullah; Rifqy Hammad (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2022)
A widely varieties of game genre already exist in the world, one of them is a platform game-type, this type of game in which players are required to jump between the Platform, through various Obstacle, so that players can survive and continue the game to the next level. This type of games have a wide variety of game mechanics such as jumping higher with the help of an object such as trampoline, beat or slay the enemy AI (Artifical Intelligent enemy) using a weapon or Environment that exist in the game, The Development of the game with fast phase in-gamemovement speed hence the player reflect will be tested, this game is 2D based, which will be made using Unity and the assets that available at Unity Store and some are creator made.